The Intention to Use Digital Banking Services among Gen Z in Indonesia Based on Technology Acceptance Model (TAM) - Meisya Nurahmasari; Syarifah Nur Silfiyah; Christian Haposan Pangaribuan (Jurnal Manajemen dan Bisnis Madani, 2023)
As information technology advances, societal demands rise, and smartphone features and sophistication rise along with them, banks must adapt to meet the current demand. For Indonesians, who are accustomed to use cash, digital banking will become new digital transformation. There is no information available on the variables that might affect Indonesians’ behavior intentions about using digital banking services. In particular, among generation Z in Indonesia following the COVID-19 outbreak, this research seeks to investigate the connection between perceived usefulness, perceived ease of use, and self-efficacy in consumers' intention for using digital banking services based on the Technology Acceptance Model (TAM). For the survey data gathered from 150 generation Z, multivariate data analysis approaches (reliability and validity test, multiple linear regression, collinearity analysis, and path estimations) are utilized. The results of this study's analysis demonstrate that perceived usefulness indicates a great influence on the attitude and intention to use digital banking services, compared to the perceived ease of use and self-efficacy. Therefore, for customers to completely comprehend the advantages associated with using digital banking services, it is critical to boost their perception of the usefulness of the services in their daily life.